A case study: understanding the perceived effect of a doctoral community college leadership program on program participants and their institution - Enders, Jessica J. (Kansas State University, 2021)
Community colleges nationwide continue to face a leadership crisis. Lack of succession planning, the dynamic leadership challenge landscape, stress, and lack of incentives to become an administrator have created leadership voids throughout entire institutions. As leaders retire and new challenges, such as the COVID-19 global pandemic, emerge, the need to lessen leadership gaps by developing and preparing the next generation of institutional leaders continues. Research has indicated a mechanism to develop leaders is through doctoral community college leadership programs (CCLP). However, there has been limited research on the effect these programs have on participants and even less on institutions sponsoring CCLP cohorts of aspiring leaders from all levels within the institution (i.e., faculty, staff, and leadership). Understanding the perceived effects of doctoral CCLPs is critical to ensure the next generation of leaders are prepared to address the challenges leaders face. Therefore, the purpose of this mixed-methods case study was to investigate the perceived effect of Kansas State University’s doctoral Community College Leadership Program (KSU-CCLP) on College of the Desert (COD) and the students enrolled in the program. Study findings revealed several benefits to all constituents. The benefits to COD included improved communication and the initiation of a culture of leadership. The benefits to the graduate students enrolled in the program included increasing their communication and problem-solving skills and being better prepared for future leadership responsibilities. In summary, this study provides evidence that the KSU-CCLP (a) is a positive return on investment for the sponsoring college and (b) prepares aspiring leaders for improved performance in their current positions and future leadership opportunities.
Keywords: Leadership; Leadership development; Community college leadership programs; Leadership crisis gap